227k views
4 votes
What is the solution to this system of equations?

x + y = 6
x = y + 4

A: (11/2, 1/2)
B: (21/2, 11/2)
C: (5, 1)
D: (1, 5)

1 Answer

0 votes

Answer:

(5, 1) (Answer C)

Explanation:

Note that the second equation features x as a function of y: x = y + 4. We can substitute y + 4 for x in the first equation, obtaining:

y + 4 + y = 6

and then, after we combine like terms,

2y = 2, or y = 1.

x = y + 4, subbing 1 for y here results in x = 1 + 4, or x = 5

The solution is (5, 1) (Answer C)

User Franz They
by
7.5k points